2019
DOI: 10.2147/opth.s219715
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comparison of anterior chamber flare among different glaucoma surgeries</p>

Abstract: PurposeTo compare postsurgical anterior chamber flare (ACF) among conventional (trabeculectomy, LEC) and novel (EX-PRESS Shunt, EXP) filtration surgeries and microhook ab interno trabeculotomy (μLOT), a novel minimally invasive glaucoma surgery (MIGS).Subjects and methodsThis retrospective study included 125 primary open angle glaucoma eyes (89 consecutive subjects) treated with μLOT (n=38), LEC (n=12), or EXP (n=75). The intraocular pressure (IOP), numbers of antiglaucoma medication, and ACF at preoperatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…We observed increased AC flare after µLOT ( Table 7 ), which returned to the preoperative level by 6 months postoperatively. As reported previously, postoperative increases in AC flare after µLOT might last longer than filtration surgery, such as Ex-PRESS shunt [ 36 ]. The loss of CECD was reported to be 6.5% 1 year after cataract surgery alone in eyes with glaucoma [ 37 ], 6.3% 2 years after trabeculectomy monotherapy [ 38 ], and 2.4% 1 year after Trabectome (combined surgery, 47%) [ 39 ].…”
Section: Discussionmentioning
confidence: 68%
“…We observed increased AC flare after µLOT ( Table 7 ), which returned to the preoperative level by 6 months postoperatively. As reported previously, postoperative increases in AC flare after µLOT might last longer than filtration surgery, such as Ex-PRESS shunt [ 36 ]. The loss of CECD was reported to be 6.5% 1 year after cataract surgery alone in eyes with glaucoma [ 37 ], 6.3% 2 years after trabeculectomy monotherapy [ 38 ], and 2.4% 1 year after Trabectome (combined surgery, 47%) [ 39 ].…”
Section: Discussionmentioning
confidence: 68%
“…However, in the latter condition, PAS may result from iris apposition on the TM, which includes trauma and increased IOP. 22 Therefore, the total PAS and PAS within the µLOT incision would develop gradually over time postoperatively because of the continuous increased outflow into Schlemm’s canal within the incision, which induces iris apposition on the TM. Inflammation associated with surgery might contribute to PAS formation; however, we did not detect this because aqueous flare, which is used to estimate postoperative inflammation, was not associated significantly with the PAS rate.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, the postoperative AC flare was 6.3 pc/ms, which is within range of the baseline level. In another study, it was reported that the postoperative AC flare after μLOT returned to baseline at 1 month and was significantly lower compared with that associated with trabeculectomy at 6 months 38 . In the present study, we did not monitor the patients for AC cell or flare quantitatively, so additional study using lase flare-cell meter will be needed for quantitative analysis 39 ; however, there were no significant differences in postoperative inflammation graded by SUN working group criteria between the non-steroid and steroid groups, and none of the eyes in either group showed prolonged inflammation at 1 week requiring additional anti-inflammatory medications.…”
Section: Discussionmentioning
confidence: 93%